2018
DOI: 10.15210/lepaarq.v15i30.13157
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de materiales artísticos mediante espectroscopia infrarroja por reflectancia total atenuada

Abstract: este trabajo describe el análisis por espectroscopia infrarroja utilizando la técnica de reflectancia total atenuada de pinturas al óleo y acrílicas comerciales conteniendo blanco de titanio, azul de Prusia y verde de ftalocianina como pigmentos.  Las pinturas al óleo con azul de Prusia mostraron la presencia de cargas como carbonato de calcio y sulfato de bario. El análisis de una réplica de una pintura acrílica con blanco de titanio sobre la que se aplicó una capa de barniz Paraloid B-67 dio un espectro infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…In all three bioreactors, vinyl bond (Albertsson et al 1987 ; Harshvardhan and Jha 2013 ; Fotopoulou and Karapanagioti 2015a ) and ester linkage (Fotopoulou and Karapanagioti 2012 ) were observed. Peak at 1066 cm −1 found in R1 and R2 was also referred by Frost et al ( 1998 ) and Guerrero and Maier ( 2018 ) who studied dimethyl sulfoxide intercalated kaolinites and barium sulfate, respectively. In R1, C-O stretching of ether group (Gajendiran et al 2016 ) at 1081 cm −1 from day 5 while 1085 cm −1 on day 33 was also observed by Prasad et al ( 2011 ) who studied radiation damage in PET polymer.…”
Section: Resultssupporting
confidence: 75%
“…In all three bioreactors, vinyl bond (Albertsson et al 1987 ; Harshvardhan and Jha 2013 ; Fotopoulou and Karapanagioti 2015a ) and ester linkage (Fotopoulou and Karapanagioti 2012 ) were observed. Peak at 1066 cm −1 found in R1 and R2 was also referred by Frost et al ( 1998 ) and Guerrero and Maier ( 2018 ) who studied dimethyl sulfoxide intercalated kaolinites and barium sulfate, respectively. In R1, C-O stretching of ether group (Gajendiran et al 2016 ) at 1081 cm −1 from day 5 while 1085 cm −1 on day 33 was also observed by Prasad et al ( 2011 ) who studied radiation damage in PET polymer.…”
Section: Resultssupporting
confidence: 75%